Effectiveness of an author’s program for psychopedagogical support in the development of metacognitive abilities - Popandopulo, Anar; Kudysheva, Ainash; Kudarova, Nazgul; Matayev, Berik; Antikeyeva, Samal (International Journal of Evaluation and Research in Education (IJERE), 2025)
In the context of the updated educational system emphasizing autonomy and critical thinking among students, it is necessary to develop effective approaches to support and enhance students’ metacognitive abilities. This research aims to evaluate the effectiveness of a proprietary psychological and pedagogical support program designed to develop metacognitive abilities in schoolchildren. Methods included conducting a quasi-experimental study with control and experimental groups, utilizing the metacognitive awareness assessment questionnaire (MAAQ) to assess outcomes. The study involved 184 students (grades 7-9; M=14.40; SD=0.81) from a school in Kazakhstan, where the experimental group underwent the intervention program. Statistical analysis revealed significant improvements in metacognitive abilities among students in the experimental group compared to the control group, including enhancements in self-awareness, self-regulation, critical thinking, decision-making, and problem-solving. These findings affirm the feasibility of integrating metacognitive approaches into educational programs and suggest further avenues for research in pedagogical support and student development.